Upaya Meningkatkan Kemampuan Menulis Permulaan Melalui Media Teka-Teki Silang Bergambar Usia 5-6 Tahun : - Rosnani, Melli; Bukman Lian; Mardiana Sari (Universitas Lancang Kuning, 2023)
This study aims to determine the improvement of early writing skills through illustrated crossword puzzles for the ages of 5-6 years in Mutiara Hati PAUD. The research location was carried out at Mutiara Hati PAUD, the address was Jalan Sei Rengit, RT. 14 RW. 05 Talang Dabuk, Banyuasin Regency, South Sumatra Province. The population is 42 children and the research sample is group B children, especially in class B2, totaling 20 children where there are 8 boys and 12 girls with an age range of 5-6 years. The research uses quantitative and qualitative methods with an action research model according to Kemmis and Taggart which focuses on children's early writing skills. The results of the research on the early writing ability of children in the first cycle obtained an average developmental achievement level (TCP) score of 9.8 in the category of starting to develop. Furthermore, it can be seen in the first cycle that the average score of developmental achievement level (TCP) of children's early writing ability gets a score of 30.75 and in the pre-cycle the score is 20.95, this indicates an increase. While in the second cycle, the overall writing ability of the children was 41.4 in the category of developing according to expectations. So that in the second cycle there was an increase of 10.65. So it was concluded that at the end of the second cycle, the research was said to be successful because the success criteria had been reached according to the agreement between the researcher and the collaborator.